An Analysis of Investor Legal Protection Against Losses Resulting from System Disruptions in Electronic Stock Transactions - Sinatra, Tristan Canari Joseph; Djajaputra, Gunawan (Jurnal Ilmu Hukum Kyadiren, 2026)
The digitalization of the Indonesian capital market, while promising easy access and efficient electronic stock transactions, actually makes investors vulnerable to system disruptions such as broker application downtime or IDX server failures. This research uses a normative-juridical research method. Legal frameworks such as the Capital Market Law, the Financial Services Authority (OJK) Law, and the Electronic Information and Transactions (ITE) Law appear normatively comprehensive, but fail to provide substantive protection due to weak enforcement, minimal standards for proportional compensation, and reliance on technical evidence that is difficult for investors to obtain. Responsible providers often escape accountability through the pretext of force majeure, while the OJK, as a regulator, is less proactive in technology audits and strict sanctions, shifting the burden of risk to novice investors. Settlement through LAPS-SJK mediation or litigation is also ineffective, as the process is asymmetric and rarely results in real justice. Urgent reforms are needed, mandating transparency in digital infrastructure and automatic redress mechanisms to prevent losses from this technological innovation.